2019
DOI: 10.1097/cm9.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

Facial aesthetic fat graft retention rates after filtration, centrifugation, or sedimentation processing techniques measured using three-dimensional surface imaging devices

Abstract: Objective: How to increase the long-term retention rate of autologous fat grafting has been widely discussed. This study aimed to evaluate long-term fat graft retention rates for the most widely used fat processing methods in the area of facial esthetic surgery, including centrifugation, filtration, and sedimentation, using three-dimensional (3D) imaging. Data Sources: PubMed, Embase, Wiley/Cochrane Library, and Web of Science databases were comprehensively searched fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…1 Autologous fat grafting is widely utilized for reconstructive and esthetic purposes, such as increasing the quality of skin, softening scar tissue, filling a soft-tissue defect, and increasing the projection of body parts, 2 , 3 because it is easily available, biocompatible, natural looking, and non-immunogenic. 4 However, the major obstacle of using fat grafts is the unpredictable and often low graft survival rate, which represents a significant burden for patients, surgeons, and healthcare systems, leading to multiple supplemental surgeries and increased treatment-associated costs. 5 Inadequate tissue vascularization is the main cause of low graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…1 Autologous fat grafting is widely utilized for reconstructive and esthetic purposes, such as increasing the quality of skin, softening scar tissue, filling a soft-tissue defect, and increasing the projection of body parts, 2 , 3 because it is easily available, biocompatible, natural looking, and non-immunogenic. 4 However, the major obstacle of using fat grafts is the unpredictable and often low graft survival rate, which represents a significant burden for patients, surgeons, and healthcare systems, leading to multiple supplemental surgeries and increased treatment-associated costs. 5 Inadequate tissue vascularization is the main cause of low graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…There was a mean score of 7.13 ± 1.81 in the filtered and washed group in our study, while it was 7.7 ± 0.6 and 8.0 ± 1.0, respectively, in the study conducted by Botti et al, 9 Both our study and Botti et al, agreed that there was no difference between the two preparation techniques. Asilian et al, 14 also concluded that there was no difference between the two methods when it came to patient satisfaction; 87.5% and 94% for centrifuged grafts and filtered/washed grafts (p= 0.468), respectively, a conclusion that was shared by the systematic review conducted by Wang et al 15 Conversely, Fulton et al, actively proposed centrifugation as a safe and effective means for preparing the fat graft and reported very good results with the process but did not compare it to any other processing technique. 16 El Sayed et al, stated that traumatic injury to blood vessels during graft harvesting results in extravasation of blood cells into the graft, which may induce an inflammatory reaction at the recipient site; such blood components may not be removed by filtration, and the centrifugation process was thus proposed as the go-to fat graft processing technique.…”
Section: Discussionmentioning
confidence: 95%
“…The overall visible volumetric effect up to 1 year after grafting observed in our study matches the observed overall effect in previous studies using three-dimensional stereophotogrammetry. 7,10,[12][13][14]21 A one-to-one comparison of the observed effects in the various studies is difficult to perform because of differences in injected volumes, fat grafting techniques, and different evaluated regions between the studies. Notwithstanding these differences in design of the studies, similar effects were reported in general.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of three-dimensional stereophotogrammetry in the clinical setting, this technique has evolved to be the leading tool for assessing visible volumetric effects as a function of time. 4,[7][8][9] Most clinical studies used three-dimensional stereophotogrammetry to assess the overall visible volumetric effect (i.e., the volumetric effect of the total face). 10,11 Occasionally, attempts have been made to assess local effects too, by manually selecting large, not strictly predefined areas on three-dimensional images.…”
mentioning
confidence: 99%